Metatranscriptomics Reveals the Functions and Enzyme Profiles of the Microbial Community in Chinese Nong-Flavor Liquor Starter - Huang, Yuhong; Yi, Zhuolin; Jin, Yanling; Huang, Mengjun; He, Kaize; Liu, Dayu; Luo, Huibo; Zhao, Dong; He, Hui; Fang, Yang; Zhao, Hai (Frontiers in Microbiology, 2017)
Chinese liquor is one of the world’s best-known distilled spirits and is the largest spirit category by sales. The unique and traditional solid-state fermentation technology used to produce Chinese liquor has been in continuous use for several thousand years. The diverse and dynamic microbial community in a liquor starter is the main contributor to liquor brewing. However, little is known about the ecological distribution and functional importance of these community members. In this study, metatranscriptomics was used to comprehensively explore the active microbial community members and key transcripts with significant functions in the liquor starter production process. Fungi were found to be the most abundant and active community members. A total of 932 carbohydrate-active enzymes, including highly expressed auxiliary activity family 9 and 10 proteins, were identified at 62 °C under aerobic conditions. Some potential thermostable enzymes were identified at 50°C, 62 °C and 25°C (mature stage). Increased content and overexpressed key enzymes involved in glycolysis and starch, pyruvate and ethanol metabolism were detected at 50 and 62 °C. The key enzymes of the citrate cycle were up-regulated at 62 °C, and their abundant derivatives are crucial for flavor generation. Here, the metabolism and functional enzymes of the active microbial communities in NF liquor starter were studied, which could pave the way to initiate improvements in liquor quality and to discover microbes that produce novel enzymes or high-value added products.